What is an ebook? What is a Book App? And Why Should We Care? An Analysis of Contemporary Digital Picture Books. - Sargeant, Betty (Children's Literature in Education, 2015)
Book apps have developed into a new format for the picture book. Given the crucial role that picture books have played in early childhood education, it seems pertinent to ascertain the ways in which they have been affected by digitisation. In response to concerns regarding a lack of models and design principles within children's digital publications, this transdisciplinary study attempts to go some way towards addressing the need for more research in this area. The article draws on research into children's literature and human-computer interaction, analysing a range of digital picture books and arguing that people read ebooks, whereas they use book apps, the latter being far more media-rich and interactive. The article also uncovers ways in which designers can use media-rich interactive features to further children's engagement with their literature.